Association Between Variants in Calcineurin Inhibitor Pharmacokinetic and Pharmacodynamic Genes and Renal Dysfunction in Adult Heart Transplant Recipients - Oreschak, Kris; Saba, Laura M.; Rafaels, Nicholas; Ambardekar, Amrut V.; Deininger, Kimberly M.; Page, Robert L.; Lindenfeld, JoAnn; Aquilante, Christina L. (Frontiers in Genetics, 2021)
Background: The goal of the study was to assess the relationship between single nucleotide variants (SNVs) in calcineurin inhibitor (CNI) pharmacokinetic and pharmacodynamic genes and renal dysfunction in adult heart transplant (HTx) recipients. Methods: This retrospective analysis included N=192 patients receiving a CNI at one-year post-HTx. Using a candidate gene approach, 93 SNVs in eight pharmacokinetic and 35 pharmacodynamic genes were chosen for investigation. The primary outcome was renal dysfunction one-year after HTx, defined as an eGFR <45 mL/min/1.73m2. Results: Renal dysfunction was present in 28.6% of patients one-year after HTx. Two SNVs [transforming growth factor beta 1 (TGFB1) rs4803455 C>A and phospholipase C beta 1 (PLCB1) rs170549 G>A] were significantly associated with renal dysfunction after accounting for a false discovery rate of 20%. In a multiple-SNV adjusted model, variant A allele carriers of TGFB1 rs4803455 had lower odds of renal dysfunction compared to C/C homozygotes (OR 0.28, 95% CI 0.12-0.62; p=0.002), whereas PLCB1 rs170549 variant A allele carriers had higher odds of the primary outcome versus patients with the G/G genotype (OR 2.66, 95% CI 1.21-5.84, p=0.015). Conclusions: Our data suggest that genetic variation in TGFB1 and PLCB1 may contribute to the occurrence of renal dysfunction in HTx recipients receiving CNIs. Pharmacogenetic markers, such as TGFB1 rs4803455 and PLCB1 rs170549, could help identify patients at increased risk of CNI-associated renal dysfunction following HTx, potentially allowing clinicians to provide more precise and personalized care to this population.